DESENVOLVIMENTO DE UM BIOSSENSOR AMPEROMÉTRICO PARA DETERMINAÇÃO DE TRIGLICERÍDEOS EM BIODIESEL - Leal, Romario Cardoso (2014)
A biossensor was developed for determination of triglycerides in biodiesel. The biossensor was prepared by immobilizing peroxidase obtained from a crude extract of zucchini on carbon paste. Studies was realized with intention to optimization experimental condition, including, graphite:mineral oil ratio, concentration of immobilized enzymes and stability for the biosensor and pH studies, working potential and concentration of the mediator to bulk solution. The best ratio found was 75:25 graphite:mineral oil and 212 U.mLˉ¹ to biosensor. The best response wasobserved at pH 6.5, working potential -0.075 V and 272.4 μmol/L of mediator hydroquinone. The sample was prepared by extracting biodiesel present in the sample in a mixture of 0.8 mL of absolute ethanol, 0.8 ml of distilled water and 1.6 ml of heptane and triglyceride after separation of the phases, an aliquot of 1 ml of enzyme reagent was added to an aliquot of 0.3 ml of the organic phase for the conversion of the triglyceride to hydrogen peroxide. The hydrogen peroxide formed was extracted using 6 mL of phosphate buffer 0.1 mol Lˉ¹ pH 6.5 and 9 ml of chloroform. Then, the mediator hydroquinone was added to the solution and measured the concentration of hydrogen peroxide present in the sample in triplicate. The analytical curves showed good linearity in the range up to 281 mmol.Lˉ¹ with a coefficient of linearity (r) = 0.998. The biosensor showed to be very sensitive to the analyte with the values for the limit of detection and quantification 1.98 x10ˉ⁹ mol Lˉ¹ and 5.93 x10ˉ⁹ mol Lˉ¹ respectively.